A SELF-REFLECTION IN DEVELOPING TEACHING PERFORMANCE AT THE CLASSROOM FOR ENGLISH FOREIGN LANGUAGE (EFL) TEACHERS - Esih Karlinawati (University of Muhammadiyah Purwokerto, 2014)
This paper deals with a topic self-reflection in developing teaching performance. Self-reflection is a vital skill to reflect and evaluate teachers’ teaching performance in the classroom. However, there are many teachers running monotonous classes because they do not make a self-reflection. This consideration explores teachers’ strengths and weaknesses in learning process. This research will help the teachers to maintain or eliminate critical incident on learning and teaching process. This research had been conducted at English Education Department, University of Muhammadiyah Yogyakarta. The respondents consist of some English Foreign Language (EFL) teachers. This research used qualitative research design. Then the researcher used interview as a research instrument to elaborate the information. The data becomes the parameter whether the respon-dents give agreements or disagreements to the case in using self-reflection. Considering the reasons above, the researcher makes an implication that self-reflection can be a good method for EFL teachers. The finding reveals that teachers who use self-reflection get better ways on how to explore well performance in the class-room. Writing journal is a kind of reflective language teaching that has been employed to enhance teachers’ skill in teaching. Therefore, self-reflection is also to engage systematic reflection on teaching. Keywords: Self-Reflection, Professional Development, Teaching Performance, Teaching Reflective